Optimizing Public Service Quality Through the Implementation of the E-Court Application in Class 1A District Court of Batam City - Vernanda Handini; Lubna Salsabila; Karol Teovani Lodan; Timbul Dompak (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
The implementation of digital technology in the judiciary system has become a cornerstone of public service improvement. This study examines the effectiveness of the E-Court application in optimizing public service quality at the Class 1A District Court of Batam City. The research employs a qualitative approach, utilizing data gathered through interviews, observations, and document analysis. Findings indicate that the E-Court application significantly enhances the accessibility, efficiency, and transparency of court services by reducing processing times, minimizing manual paperwork, and fostering accountability. However, challenges such as technical limitations, digital literacy gaps, and resource constraints impede its full potential. Recommendations include infrastructure enhancement, comprehensive user training, and policy support to maximize the benefits of digital integration in public service delivery. This study contributes to understanding the transformative role of technology in judicial administration and its impact on public satisfaction.